Aflatoxins, major contributions to harvest loss - what do we know and not know? - Lindahl, Johanna F.; Grace, Delia (2013)
In high-income countries, contamination of crops pre or post-harvest with mycotoxin-producing fungi cause substantial financial losses, with mega-tons of crops every year exceeding the allowed limits and therefore being disregarded as human and animal food. It is estimated that applying the US and the EU regulatory limits to corn would cause losses of 40 to 124 million USD respectively, only in the three most important corn exporting countries. To this is added costs of destroying crop, which may amount to 50% of the corn harvest in some years. In low-income countries, limited food resources and lack of awareness, prevents many smallholders from discarding damaged, and infected food products. A climate that promotes fungal growth and suboptimal storage procedures contribute to the extensive aflatoxin contamination in these countries.